1994
DOI: 10.1088/0953-8984/6/15/010
|View full text |Cite
|
Sign up to set email alerts
|

The peculiarities of glass state formation and the role of random elastic fields in mixed crystals of the KH2PO4family

Abstract: The source of random static electrical fields, which is determined by both the piezoelectric coupling and the static elastic deformations induced by substitutional disorder of ions with different ionic radii has been considered for mixed crystals of the KH2PO4 family. It is shown that the random electrical fields act mainly on the lattice polarization along the c axis and up-down proton configurations. The short-range interactions of four acid protons surrounding a PO4 group are represented as the random local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…It is observed that d 36 increases with the increase in deuterium content, and this trend for d 14 is slight. In mixed crystals of the KDP family, the piezoelectric coupling of polarization and elastic strain u 6 is the source of the random electric fields along the c axis which play an essential role in these crystals (Smolyaninov & Glinchuk, 1994;Levitskii & Lisnii, 2004). To clarify the deformation of the PO 4 tetrahedron due to substitution of D for H, the structures of some crystals were resolved by single-crystal X-ray diffraction.…”
Section: Figurementioning
confidence: 99%
“…It is observed that d 36 increases with the increase in deuterium content, and this trend for d 14 is slight. In mixed crystals of the KDP family, the piezoelectric coupling of polarization and elastic strain u 6 is the source of the random electric fields along the c axis which play an essential role in these crystals (Smolyaninov & Glinchuk, 1994;Levitskii & Lisnii, 2004). To clarify the deformation of the PO 4 tetrahedron due to substitution of D for H, the structures of some crystals were resolved by single-crystal X-ray diffraction.…”
Section: Figurementioning
confidence: 99%
“…The chaotic static electric fields governed by the piezoelectric interactions and static elastic strains are believed [27] to be formed by chaotic substitutional disorder of ions of different radii. It has been shown that these fields act, mainly, on the lattice polarization along the c-axis and on the configurations with two protons near the "upper" or "lower" (with respect to the c-axis) oxygen atoms.…”
Section: Glass Phase Composition Regionmentioning
confidence: 99%
“…Цi поля викли-канi структурним безладом завдяки рiзницi мiж iонними радiусами iонiв Rb i NH 4 [11]. В [6] показано, що в присутностi гаусових ви-падкових полiв з нульовим середнiм значенням перехiд в протонне скло є розмитий, тобто сприйнятливiсть є згладжена, а параметр по-ICMP-05-01U 2 рядку протонного скла залишається скiнченним при температурах, вищих вiд номiнальної температури заморожування (межа стабiль-ностi реплiчно-симетричного розв'язку).…”
Section: вступunclassified